2017
DOI: 10.1097/meg.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

The impact of value-based healthcare for inflammatory bowel diseases on healthcare utilization: a pilot study

Abstract: Background and objectives Value-based healthcare (VBHC) is considered to be the solution that will improve quality and decrease costs in healthcare. Many hospitals are implementing programs on the basis of this strategy, but rigorous scientific reports are still lacking. In this pilot study, we present the first-year outcomes of a VBHC program for inflammatory bowel disease (IBD) management that focuses on highly coordinated care, task differentiation of providers, and continuous home monitoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 11 publications
0
50
0
Order By: Relevance
“…In Europe, a value-based health care model focused on coordinated care, task differentiation of providers, and continuous home monitoring (using mobile health technologies) showed significantly fewer upper endoscopies, surgeries, hospitalizations, and emergency room visits compared with matched controls. 13,117,118 IBD-related costs were 16% ($771 per patient) less than expected during the 1-year study period. 13 Large health systems also have begun to develop telecommunications and telehealth programs as described in a recent review by Cross and Kane 119 to take care of the "whole patient".…”
Section: Examples Of Integrated Inflammatory Bowel Disease Care Withimentioning
confidence: 73%
“…In Europe, a value-based health care model focused on coordinated care, task differentiation of providers, and continuous home monitoring (using mobile health technologies) showed significantly fewer upper endoscopies, surgeries, hospitalizations, and emergency room visits compared with matched controls. 13,117,118 IBD-related costs were 16% ($771 per patient) less than expected during the 1-year study period. 13 Large health systems also have begun to develop telecommunications and telehealth programs as described in a recent review by Cross and Kane 119 to take care of the "whole patient".…”
Section: Examples Of Integrated Inflammatory Bowel Disease Care Withimentioning
confidence: 73%
“…The Division of Digestive Disease at UCLA has introduced a comprehensive, integrated, and holistic approach to value-based care in the chronic disease management of Inflammatory Bowel Diseases (IBD), with the development of the “Value- Quotient” (or vQ) for value-based and cost-effective IBD management. 2225 The Illinois Gastroenterology Group developed Project Sonar, a care management solution for patients with IBD. Project Sonar utilizes nurse care managers and physician medical directors in a team approach to coordinate care for patients with IBD, along with clinical decision support and patient engagement, and has recently partnered with a national payer to create a specialist intensive medical home.…”
Section: Discussionmentioning
confidence: 99%
“…Hoffenberg et al[10] found that one-fifth ER visits for IBD were judged medically unnecessary, and one-half avoidable in a more optimal health care system. van Deen et al [23]. reported that IBD patients treated with the value-based healthcare program, which focuses on highly coordinated care, task differentiation of provider, and continuous home monitoring achieved significantly fewer ER visits…”
Section: Discussionmentioning
confidence: 99%